REVITALISASI PESANTREN SEBAGAI AGEN HUMAN RESOURCES BUILDING - Suwarno Suwarno (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
Pesantren (Islamic boarding schools) with their long historical journey have proved themselves not only as learning institutions still surviving to this day, but also as such a symbol of the power of culture and socio-religious diversity. Public confidence and very high expectations in regard with the birth of generations being able to bridge the building of knowledge on one hand and the great noble characters on the other hand, have still been devoted to the religious educational institutions. By photographing the long history of pesantren, their typology of learning and their presence amid competitive educational institutions today, this article tries to offer a concept aimed at revitalizing the pesantren to purposefully respond to the demands and expectations of their stakeholders. Efforts to reform the curriculum, build human resources capacity, and develop the learning system management could be carried out in revitalizing the role of pesantren.Keywords: Pesantren, human resources, curriculum